Evaluation of Customer Service and Performance in Community-Managed Water Supply Systems in Jhapa District, Nepal - Guragain, Madhav Prasad; Mbonigaba, Celestin (Apex Journal of Business and Management, 2025)
Ensuring access to clean and safe drinking water is a fundamental human right, particularly in developing countries where centralized infrastructure is limited. In Nepal, community-managed water supply systems play a crucial role in providing water services to rural and peri-urban areas. This study aims to evaluate the satisfaction of customer based on five community-managed water supply systems in Jhapa District, Nepal, focusing on key performance indicators such as service coverage, water quality, and user satisfaction. Data was collected from five community-managed water supply systems: Pathivara-Lakhanpur, Gauradaha, Goldhap, Shree Bhawani, and Baniyani. The analysis focused on service coverage, and water consumption. Service coverage varied significantly across the systems, from 42.38% in Baniyani to 98.49% in Shree Bhawani, with an average coverage of 67.9%. Water Consumption Per capita water consumption was below the national standards, averaging 18.58 Liters Per Capita per Day (LPCD), with Shree Bhawani having the highest at 21.92 lpcd and Goldhap the lowest at 13.7 lpcd. Satisfaction levels varied, with Goldhap achieving the highest satisfaction rate of 93.94% and Shree Bhawani the lowest at 78.69%. On average, 86.45% of users were satisfied. The performance of community-managed water supply systems in Jhapa District varies significantly. While most systems perform well in terms of user satisfaction, service coverage.